2014
DOI: 10.1093/heapol/czu050
|View full text |Cite
|
Sign up to set email alerts
|

Distressed financing of household out-of-pocket health care payments in India: incidence and correlates

Abstract: Out-of-pocket (OOP) health care payments financed through borrowings or sale of household assets are referred to as distressed health care financing. This article expands this concept (to include contributions from friends or relatives) and examines the incidence and correlates of distressed health care financing in India. The analysis finds a decisive influence of distressed financing in India as over 60 and 40% of hospitalization cases from rural and urban areas, respectively, report use of such coping strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 29 publications
3
88
2
1
Order By: Relevance
“…Many countries are trying to control the ever-increasing of public financing that make the OOP unceasingly increase. Rural and urban area’s patients in India have poverty health care financing are 40% and 60% respectively [27]. The Portuguese scholars believed that the huge medical expenses were in urgent need to cut down that used to risk resistance in elderly people cannot afford [28].…”
Section: Discussionmentioning
confidence: 99%
“…Many countries are trying to control the ever-increasing of public financing that make the OOP unceasingly increase. Rural and urban area’s patients in India have poverty health care financing are 40% and 60% respectively [27]. The Portuguese scholars believed that the huge medical expenses were in urgent need to cut down that used to risk resistance in elderly people cannot afford [28].…”
Section: Discussionmentioning
confidence: 99%
“…The survey elicits information regarding the major source of financing to capture whether bulk of the out of pocket expenditure was incurred via distressed means or not. The component such as borrowings (with or without interest), contribution from friends and relatives (with or without repaying option) and sale of assets is combined defined as distressed financing [27, 46]. …”
Section: Methodsmentioning
confidence: 99%
“…36,812 for the entire cancer therapy excluding non-medical costs [24]. It is also noted that out of pocket (OOP) expenditure on cancer hospitalization is about 2.5 times of overall average hospitalization expenditure [27]. While catastrophic expenditure on cancer inpatient treatment is highest among all NCDs, poor health financing mechanisms and heavy reliance on out-of-pocket healthcare payments compels several cancer patients to resort to distressed means for treatment financing [2830].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, using the 60 th health round of the NSS, researchers find that outpatient care is more impoverishing than inpatient care in urban and rural areas alike [2]. Another study shows that OOP payments on outpatient visits are mostly met through own income and savings raising the issue of ability-to-pay as a determinant of health-seeking behaviour for OPD [5]. Yet another study [6] showed that 3.5 percent of the population fell below the poverty line on account of OOPS, but this fell to 0.5 percent if OOP payments on outpatient care are excluded, with implications about the need for comprehensive coverage schemes that should include drugs or outpatient care in general.…”
Section: Introductionmentioning
confidence: 99%